Critical clearing time estimation using synchrophasor data‐based equivalent dynamic model. Issue 7 (1st April 2015) - Paul, Avishek; Senroy, Nilanjan
Abstract : A critical aspect of online dynamic security assessment is the ranking of probable contingencies based on the critical clearing time. Ordinarily critical clearing time involves simulation of contingencies requiring extensive computational resources and updated network data. This study proposes to use reduced order equivalents of the network around a critical tie line, to estimate the critical clearing time. It is proposed to derive the reduced order model from synchrophasor data in real time, so as to replicate the most updated system dynamics. The stability margins in the reduced order model and the original detailed model are correlated using a transient energy function that considers the kinetic and potential energy gained by any system during a fault. It is shown that it is possible to arrive at a relatively accurate estimate of the critical clearing time of a contingency in the detailed model, using the equivalent model obtained using synchrophasors data.